The past of Hungarian anthropology and future objectives - Farkas, Gyula L. (Acta Biologica Szegediensis, 2000)
The author lists the goals drawn up by Aurél Török upon establishing Hungarian anthropology. Based on these, he first outlines the history of the establishment of university institutes, collections, scientific associations and periodicals, then lists the places and fields of research of Hungarian anthropology. The author describes the connection of Hungarian anthropology with the Hungarian Academy of Sciences and analyses the present state of the new generation of anthropologists. Based on these points the author formulates objectives for the future. Finally, he gives a chronological list of all Hungarian congresses and conferences related to anthropological research.The author lists the goals drawn up by Aurél Török upon establishing Hungarian anthropology. Based on these, he first outlines the history of the establishment of university institutes, collections, scientific associations and periodicals, then lists the places and fields of research of Hungarian anthropology. The author describes the connection of Hungarian anthropology with the Hungarian Academy of Sciences and analyses the present state of the new generation of anthropologists. Based on these points the author formulates objectives for the future. Finally, he gives a chronological list of all Hungarian congresses and conferences related to anthropological research.